Spin-label electron spin resonance study of bacteriophage M13 coat protein incorporation into mixed lipid bilayers. - Datema, K; Wolfs, C; Marsh, D; Watts, A; Hemminga, M (1987)
The major coat protein of bacteriophage M13 was incorporated in mixed dimyristoylphosphatidylcholine/dimyristoylphosphatidylglycerol (80/20 w/w) vesicles probed with different spin-labeled phospholipids, labeled on the C-14 atom of the sn-2 chain. The specificity for a series of phospholipids was determined from a motionally restricted component seen in the electron spin resonance (ESR) spectra of vesicles with the coat protein incorporated. At 30 degrees C and pH 8, the fraction of motionally restricted phosphatidic acid spin-label is 0.36, 0.52, and 0.72 for lipid/protein ratios of 18, 14, and 9 mol/mol, respectively. The ESR spectra, analyzed by digital subtraction, resulted in a phospholipid preference following the pattern cardiolipin = phosphatidic acid greater than stearic acid = phosphatidylserine = phosphatidylglycerol greater than phosphatidylcholine = phosphatidylethanolamine. The specificities found are related to the composition of the target Escherichia coli cytoplasmic membrane.